Unreliable narration and trustworthiness: intermedial and interdisciplinary perspectives - Nünning, Vera (Narratologia, 2015)
"Initiating a transgeneric, intermedial and interdisciplinary approach to narrative unreliability, this volume is meant to enrich, modify and refine our understanding of (un)reliable narration by taking into account not only different genres and media, but also research in a variety of disciplines. The three sections of the volume comprise articles on the theory of unreliable narration, transgeneric and intermedial issues as well as studies from areas such as journalism, politics, law and medicine" --
Literaturangaben
Keywords: Aufsatzsammlung; Konferenzschrift -- 2013 -- Mainz; Unzuverlässigkeit; Erzähler